Knowledge and Family Support Regarding Regular Medication Taking in Tuberculosis Resistant Patients - Qurrotu'ain, Nadia Luthfiyah; Lubis, Erika; Dewi, Aliana; Widiasari, Widiasari (Health Information : Jurnal Penelitian, 2023)
Knowledge and family one factor in success treatment of Multidrug-Resistant Tuberculosis (MDR TB), and is support orientation to function enhancement regularity in take anti- tuberculosis medication (OAT). Regularity is behavior Good especially in drink medication that has been given. Patient Resistant Tuberculosis (R-TB) is patients who do not complete drink drug so that bacteria the develop which results resistant. Study aim For know connection knowledge and support family to regularity taking OAT in R-TB patients at Persahabatan Hospital . Study with cross sectional technique . Sample of 104 respondents with purposive sampling method . Research results univariate showing majority 46-55 years old , male , college high or not working . Analysis results bivairat Spearman's rho method is obtained exists relationship knowledge and family with regularity drink medication in patients resistance tuberculosis . Advice on the need improved awareness in patients , evidence support family That real during operate treatment period long and digging related matters with regularity drink medicine .